Presence of American Cutaneous Leishmaniasis Vectors Surrounding the City of Medellín, Colombia (2002)
ABSTRACT: The presence of Lutzomyia (Helcocyrtomyia) hartmanni, as a vector of Leishmania colombiensis and L. columbiana (Verrucarum group), recently incriminated in the transmission of leishmaniasis, and L. pia (Verrucarum group) are reported for the first time in a periurban area of Medellín city. There is thus a risk of leishmaniasis transmission in this town.